2013
DOI: 10.1155/2013/942972
|View full text |Cite
|
Sign up to set email alerts
|

Does Fundus Fluorescein Angiography Procedure Affect Ocular Pulse Amplitude?

Abstract: Purpose. This study examines the effects of fundus fluorescein angiography (FFA) procedure on ocular pulse amplitude (OPA) and intraocular pressure (IOP). Materials and Methods. Sixty eyes of 30 nonproliferative diabetic retinopathy patients (15 males, 15 females) were included in this cross-sectional case series. IOP and OPA were measured with the Pascal dynamic contour tonometer before and after 5 minutes of intravenous fluorescein dye injection. Results. Pre-FFA mean OPA value was 3.05 ± 1.36 mmHg and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Pekel et al evaluated choroidal changes after FFA using dynamic contour tonometry that measured changes in IOP and ocular pulse amplitude (OPA), and reported that both mean IOP and OPA values decreased following FFA, though difference was not statistically significant (20) In the present study, we used OCT device, a noninvasive diagnostic and monitoring tool for chorioretinal diseases (21), to detect possible changes following angiographic procedures. We found no significant differences in CT before and after FFA; however, there were significant differences in CT following ICGA.…”
Section: Discussionmentioning
confidence: 86%
“…Pekel et al evaluated choroidal changes after FFA using dynamic contour tonometry that measured changes in IOP and ocular pulse amplitude (OPA), and reported that both mean IOP and OPA values decreased following FFA, though difference was not statistically significant (20) In the present study, we used OCT device, a noninvasive diagnostic and monitoring tool for chorioretinal diseases (21), to detect possible changes following angiographic procedures. We found no significant differences in CT before and after FFA; however, there were significant differences in CT following ICGA.…”
Section: Discussionmentioning
confidence: 86%
“…Conventional diagnostic tools for DR are Fluorescence Angiography (FA), Optical Coherence Tomography (OCT) and Colour Fundoscopy (CF). FA is an invasive technique and often results in post-test complications to patients due to the usage of the dye [9]. OCT and CF are non-invasive technique.…”
Section: Introductionmentioning
confidence: 99%